The effectiveness of TRIS and ammonium buffers in glass dissolution studies: a comparative analysis - Ramya Ravikumar; Clare L. Thorpe; Claire L. Corkhill; Sam A. Walling; James J. Neeway; Carolyn I. Pearce; Albert A. Kruger; David S. Kosson; Jose Marcial; Russell J. Hand (npj Materials Degradation)
Abstract Selecting appropriate buffers is crucial for evaluating the chemical durability of glass under controlled conditions such as in the EPA 1313 test designed to measure elemental release as a function of pH. The efficacy of two alkali-metal free buffers, TRIS (NH2C(CH2OH)3) and ammonium chloride—ammonia (NH3/NH4Cl), was investigated during EPA 1313 testing of a simulated Hanford low-activity waste borosilicate glass in the alkaline regime (pH 8.5–10.5) at varying temperatures (RT, 40 °C, and 60 °C). While both buffers maintained the desired pH at room temperature, and up to 40 °C, the effectiveness of TRIS decreased at elevated temperatures, particularly at pH 10.5. Although 11B NMR showed evidence of TRIS-B complexation, its effect on the rate of elemental release was found to be negligible under the test conditions. With ammonium buffer, the release of alkali cations was slightly elevated when compared to the same conditions with TRIS at early time points.